Recent Advances (2008–2015) in the Study of Ground Ice and Cryostratigraphy. (8th August 2016) - Gilbert, Graham L.; Kanevskiy, Mikhail; Murton, Julian B.
Abstract: Cryostratigraphy involves the description, interpretation and correlation of ground‐ice structures (cryostructures) and their relationship to the host deposits. Recent advances in the study of ground ice and cryostratigraphy concern permafrost aggradation and degradation, massive‐ice formation and evaluation of ground‐ice content. Field studies have increased our knowledge of cryostructures and massive ground ice in epigenetic and syngenetic permafrost. Epigenetic permafrost deposits are relatively ice‐poor and composed primarily of pore‐filled cryostructures, apart from an ice‐enriched upper section and intermediate layer. Syngenetic permafrost deposits are commonly identified from cryostructures indicative of an aggrading permafrost table and are characterised by a high ice content, ice‐rich cryofacies and nested wedge ice. Degradation of ice‐rich permafrost can be marked by thaw unconformities, truncated buried ice wedges, ice‐wedge pseudomorphs and organic‐rich 'forest beds'. Studies of massive ground ice have focused on wedge ice, thermokarst‐cave ice, intrusive ice and buried ice. Significant advances have been made in methods for differentiating between tabular massive‐ice bodies of glacier and intrasedimental origin. Recent studies have utilised palynology, isotope geochemistry and hydrochemistry, in addition to sedimentary and cryostratigraphic analyses. The application of remote sensing techniques and laboratory methods such as computed tomography scanning has improved estimations of the ice content of frozen sediments. Copyright © 2016 John Wiley & Sons, Ltd.